Frontline clinicians' perspectives on and utilization of trauma-focused therapy with individuals with eating disorders. Issue 1 (1st January 2017) - Trottier, Kathryn; Monson, Candice M.; Wonderlich, Stephen A.; MacDonald, Danielle E.; Olmsted, Marion P.
ABSTRACT: With this study, we sought to survey clinicians regarding their perspectives and use of concurrent or integrated psychotherapy for co-occurring eating disorders (EDs) and posttraumatic stress disorder. We conducted a quantitative survey of 184 frontline ED clinicians to investigate whether, and to what extent, they view concurrent EDs and trauma-focused therapy as clinically important. We also assessed clinicians' specific concerns regarding concurrent EDs and trauma-focused treatment, as well as barriers to implementation of an evidence-based concurrent treatment. On the whole, clinicians reported that addressing trauma-related symptoms in individuals with EDs is highly important and should be administered concurrently. Although clinicians reported anticipating many important benefits of concurrent treatment, they also reported anticipating several potential negative side effects, and they reported a number of perceived barriers to implementation. Clinicians working in hospital settings anticipated more complications, expected fewer benefits, and perceived more barriers to the administration of concurrent treatment.